A pratical guide to hybrid natural Language processing : combining neural models and knowledge graphs for NLP - Gomez-Perez, Jose Manuel (Springer, 2020)
This book provides readers with a practical guide to the principles of hybrid approaches to natural language processing (NLP) involving a combination of neural methods and knowledge graphs.